Toward a More Just Approach to Poverty Simulations. (September 2016) - Browne, Laurie P.; Roll, Susan
Poverty simulations are a promising approach to engaging college students in learning about poverty because they provide direct experience with this critical social issue. Much of the extant scholarship on simulations describe them as experiential learning; however, it appears that educators do not examine biases, assumptions, and traditions of power inherent in some traditional approaches. This is particularly problematic with poverty simulations because they are tools designed to specifically address systems of inequality and oppression. This case study describes an attempt to implement a poverty simulation and measure its longitudinal effectiveness and uses findings from this study to examine poverty simulations as contexts for experiential learning. It is argued that, when implemented without critical consideration, simulations might actually perpetuate inequality rather than empower students to address poverty through civic action.